Associations of short-term exposure to air pollution and emergency department visits for pediatric asthma in Shanghai, China. (January 2021) - Liu, Lijuan; Liu, Cong; Chen, Renjie; Zhou, Yufeng; Meng, Xia; Hong, Jianguo; Cao, Lanfang; Lu, Yanming; Dong, Xiaoyan; Xia, Min; Ding, Bo; Qian, Liling; et al.
Abstract: There is limited evidence regarding the relationship between air pollution and pediatric asthma in developing countries. This study aimed to investigate the association between short-term exposure to ambient air pollutants and pediatric asthma emergency department (ED) visits in Shanghai, China. We collected data on six criteria air pollutants (PM2.5, PM10, NO2, SO2, CO, and O3 ) and daily ED visits for pediatric asthma patients from 66 hospitals in Shanghai from 2016 to 2018. The generalized additive model combined with polynomial distributed lag model was applied to explore the associations. We fitted two-pollutant models and stratified the analyses by sex, age, and season. In total, we identified 108, 817 emergency department visits for pediatric asthma. A 10 μg/m 3 increase in the concentrations of PM2.5, NO2, SO2, and O3 was significantly associated with increased risks of pediatric asthma ED visits, with relative risk of pediatric asthma of 1.011 [95% confidence interval (CI): 1.002, 1.021], 1.030 (95%CI: 1.017, 1.043), 1.106 (95%CI: 1.041, 1.174), and 1.009 (95%CI: 1.001, 1.017), respectively. The associations of NO2 remained robust in the two-pollutant models. There were stronger associations for older children (6–18 years) and in warm seasons. The concentration-response curves for pediatric asthma and PM2.5, NO2, SO2, and O3 were steeper at lower and moderate concentrations but became flatter at higher concentrations. This analysis provided evidence that short-term exposure to air pollutants (PM2.5, NO2, SO2, and O3 ) could increase the risk of asthma exacerbations among children, and health benefits would be gained from improved air quality. Graphical abstract: Image 1 Highlights: Daily data on ED visits for pediatric asthma were collected from 66 hospitals. Elevated levels of PM2.5, NO2, SO2 and O3 were associated with increased pediatric asthma visits. Most robust associations of NO2 with pediatric asthma visits. Stronger associations in older age group and in warm seasons.